Aeromonas hydrophila Infection following Leech Therapy for the Treatment of Nipple–Areola Complex Congestion after Breast Reduction: A Case Report - Torresetti, Matteo; Peltristo, Benedetta; Taddei, Francesco Mauro Junior; Di Benedetto, Giovanni (Archives of Plastic Surgery, 2024)
Several strategies for the management of venous congestion of the nipple–areola complex (NAC) after reduction mammaplasty have been proposed. Among these, hirudotherapy represents an ancient but still effective method, even though the risk of infections related to leeches should be considered. We report a peculiar case of breast infection and sepsis after leech therapy in a patient who underwent a reduction mammaplasty. A prompt surgical debridement of the wounds and necrotic tissues associated with targeted antibiotic therapy led to a fast improvement of clinical conditions, and partial preservation of the NAC was obtained. Accurate knowledge of the clinical presentation of soft tissue infections related to leeching allows for an early diagnosis and would serve as a warning for surgeons who approach such breast cosmetic procedures.
Keywords: leech; infection; nipple–areola complex; venous congestion; reduction mammaplasty